Social learning and principal-agent problems in profit sharing contract - Sapuan N.M. (Emerald Group Holdings Ltd., 2023)
Purpose - The objectives of this study are twofold. First, to theoretically examine the profit sharing (mudarabah) contract that produces an optimal distribution of return in the presence of social learning (shuratic process) within the environment of asymmetric information. Second, to empirically investigate the optimal condition of profit sharing ratio (PSR) and social learning for profit sharing (mudarabah) contract in Islamic banking. Design/methodology/approach - Data from one of the biggest and earliest Islamic banks in Malaysia were taken as a proxy of Islamic bank. The data are collected from the period of 2009 to 2013 and it will be used for the simulation process by utilizing the genetic algorithm technique. Findings - The empirical results discovered that Islamic bank had utilized social learning in their daily activities especially in the asset side. The results also showed the trend of social learning has a positive relationship with the trend of Islamic bank?s net profit. Additionally, the results also indicated that the Islamic bank?s net profit has a positive relationship with its PSR from the profit sharing (mudarabah) financing and securities investment. Originality/value -This study is the first of its kind that investigates the implementation of the social learning process in Islamic banking operation. We also utilized the latest technique from Artificial Intelligent (AI) system, i.e. a genetic algorithm (GA) to attain an optimal value for PSR and social learning process. 2016, Emerald Group Publishing Ltd. All rights reserved.